IDEAL FUZZY NEAR-RING - Saman Abdurrahman; Na'imah Hijriati; Thresye Thresye (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2012)
In this paper will be discussed ideal near-ring, ideal fuzzy near-ring covering the relationship between ideal near-ring and ideal fuzzy near-ring.